2016
DOI: 10.18276/cej.2016.2-11
|View full text |Cite
|
Sign up to set email alerts
|

What Does Post-Exercise Proteinuria Tell Us About Kidneys?

Abstract: Objectives. Post exercise proteinuria (PEP) is found in about 20-40% of sportsmen after intensive exercise. Urinary NGAL is a new marker of tubulointerstitial kidney damage. The relationship between PEP and uNGAL has not been defined yet. In presented study a resting uNGAL as a predictor of PEP was analyzed. The changes of albuminuria after exercise were monitored to estimate a frequency and range of PEP. Methods. 40 amateur healthy runners (mean age 36.65 ±10.61 years) participating in 10-km run took part in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…These results differed from data obtained from studies on humans, which showed that transient albuminuria is common after intense exercise, especially at high temperatures, with prevalence ranging from 18% to 100%, depending on the type and intensity of exercise and temperature during exercise [5,7]. Both exertion and heat stress result in a decrease in glomerular filtration and renal blood flow (notwithstanding an increase in mean arterial pressure), which reduces urine output [8,9]. The reduction in effective renal flow to 25% leads to post-exercise albuminuria (PA).…”
Section: Introductioncontrasting
confidence: 75%
“…These results differed from data obtained from studies on humans, which showed that transient albuminuria is common after intense exercise, especially at high temperatures, with prevalence ranging from 18% to 100%, depending on the type and intensity of exercise and temperature during exercise [5,7]. Both exertion and heat stress result in a decrease in glomerular filtration and renal blood flow (notwithstanding an increase in mean arterial pressure), which reduces urine output [8,9]. The reduction in effective renal flow to 25% leads to post-exercise albuminuria (PA).…”
Section: Introductioncontrasting
confidence: 75%